Depression and Anxiety Symptoms in Headache Disorders: An Observational, Cross-Sectional Study - Leonidas Mantonakis; Ioanna Belesioti; Christina I. Deligianni; Vasilis Natsis; Euthimia Mitropoulou; Elina Kasioti; Maria Lypiridou; Dimos D. Mitsikostas (Neurology International, 2024)
Background: Headache disorders have been associated with anxiety and depressive disorders. The aim of this study was to assess symptoms of anxiety and depression in a large sample of individuals with different headache disorders (HDs) in order to determine whether their frequency differs by headache type. Methods: Consecutive individuals with headache attending a headache outpatient clinic were interviewed with the HAM-D and HAM-A, along with age, sex, and education matched non-headache individuals. Results: Individuals numbering 2673 with headache (females 71.2%) and 464 non-headache individuals (females 70.9%) were interviewed (with participation rates of 98.3% and 91.0%, respectively). Migraine was diagnosed in 49.7%, tension-type headache in 38%, cluster headache 5.2%, and medication overuse (MO) in 21.8%. Participants with HD scored more in HAM-A (OR = 4.741, CI95%: 3.855–5.831, p < 0.001) and HAM-D scales (OR = 2.319, CI95%: 1.892–2.842, p < 0.001) than non-headache individuals. Participants with chronic HDs (≥15 days with headache for ≥3 consecutive months; 52.5%) scored higher for both HAM-A (OR = 1.944, CI95%: 1.640–2.303, p < 0.001) and HAM-D (OR = 1.625, CI95%: 1.359–1.944, p < 0.001) than those with episodic HDs (33.1%), as did participants with MO vs. participants without MO (OR = 3.418, CI95%: 2.655–4.399, p < 0.001 for HAM-A, OR = 3.043, CI95%: 2.322–3.986, p < 0.001 for HAM-D). Female and low-educated participants scored higher on both scales. Conclusion: Because symptoms of anxiety and depression are substantial in people with HD, the treating physicians should look out for such symptoms and manage them appropriately.